2018
DOI: 10.5200/baltica.2017.30.08
|View full text |Cite
|
Sign up to set email alerts
|

Fine-grained quartz from cryoconite holes of the Russell Glacier, southwest Greenland – a scanning electron microscopy study

Abstract: The western ablation zone of the Greenland ice sheet is darker than the surrounding ice, because a higher amount of fine-grained particles, known as a cryoconite, occur. To date, biotic cryoconite components have gained a lot of attention, in contrast with mineral components, which have been studied to a limited extent. In this study, fine-grained quartz grains from the cryoconite holes of the Russell Glacier, southwest Greenland are, therefore, examined. Authors use scanning electron microscope to elucidate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 63 publications
(82 reference statements)
1
1
0
2
Order By: Relevance
“…Wientjes et al (2011) found that inorganic mineral material or dust in the GrIS is of local origin, i.e., from the outcropping dust in the ice-free area next to the ice margin. Similar findings were brought by the Kalińska-Nartiša et al (2017) who showed that fine-grained quartz particles in cryoconite holes on the Russell glacier are mostly of local origin, although few originate from distant sources, where dry and warm climate prevail. As the climate warms, the transport of dust from snow-free areas in the Arctic that are experiencing earlier melting of seasonal snow is a contributing source of cryoconite (Stibal et al 2012;Dumont et al 2014).…”
Section: Discussionsupporting
confidence: 81%
“…Wientjes et al (2011) found that inorganic mineral material or dust in the GrIS is of local origin, i.e., from the outcropping dust in the ice-free area next to the ice margin. Similar findings were brought by the Kalińska-Nartiša et al (2017) who showed that fine-grained quartz particles in cryoconite holes on the Russell glacier are mostly of local origin, although few originate from distant sources, where dry and warm climate prevail. As the climate warms, the transport of dust from snow-free areas in the Arctic that are experiencing earlier melting of seasonal snow is a contributing source of cryoconite (Stibal et al 2012;Dumont et al 2014).…”
Section: Discussionsupporting
confidence: 81%
“…Ar atlūzām pārklātā ledāja sānu daļa (attēla vidusdaļā) pietuvinājumā redzama nākamajā attēlā. Foto: K. Lamsters, 2017. reti pārsniedz 1 km 2 . Kā novērots Tjanšanā, kur akmeņu ledājiem kopumā raksturīgas salīdzinoši lielākas dimensijas un ātrums, ledāja virsas kustības ātrums ir tikai daži centimetri līdz 10 m gadā.…”
Section: Ledāju Klasifikācijaunclassified
“…Kalińska-Nartiša et al, 2017) daudzveidīgo smilts graudu izcelsmi un pārvietošanas aģentus: ledāju, ūdens straumes, vēju. Dažiem graudiem atrastas pazīmes, kas liecina par to tālo izcelsmi Zemes tuksnešos.…”
unclassified
“…This marginal part of the glacier is particularly dark and rich in cryoconite material (e.g. Kalińska-Nartiša et al, 2017a;Stivrins et al, 2018) that is a major contributor to the darkening of the west GIS as well. Proglacial streams flowing from the Russell Glacier create the Sandflugtdalen valley-sandur, which is a large source for wind-transported dust (Kalińska-Nartiša et al, 2017b).…”
Section: Introduction and Study Areamentioning
confidence: 99%